(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
In this paper the forecasting technique of atmospheric pollution by nitrogen dioxide based on processed data of monitoring over the quantity of nitrogen dioxide and methodological characteristics for 2005–2007 in Yerevan is discussed. The "method of recognition of images" has been applied for developing the technique for warm and cold periods. Air temperature, wind direction and velocity, air humidity and inversion have been considered as predictors. Test computation has been done. For the application of the technique further tests will be carried out.